Timing of antiretroviral therapy initiation after diagnosis of recent human immunodeficiency virus infection and CD4+ T-cell recovery. (March 2016) - Ding, Y.; Duan, S.; Wu, Z.; Ye, R.; Yang, Y.; Yao, S.; Wang, J.; Xiang, L.; Jiang, Y.; Lu, L.; Jia, M.; Detels, R.; et al.
Abstract: We retrospectively examined the timing of antiretroviral therapy (ART) initiation and CD4 + T-cell recovery over 36 months among recent human immunodeficiency virus (HIV) infections using BED (HIV-1 subtypes B, E and D) immunoglobulin G capture enzyme immunoassay (BED-CEIA). Regardless of baseline CD4 + counts, individuals ( n  = 393) who initiated ART >2 months after diagnosis had significantly decreased probability and rate of achieving CD4 + counts ≥900 cells/μL or ≥600 cells/μL than those individuals ( n  = 135) who started ART earlier (≤2 months). But the mean CD4 + counts in two groups converged after 30 months of treatment. Early ART initiation leads to accelerated CD4 + recovery, but does not offer a long-term advantage in CD4 + counts.